Lipitension and cardiometabolic risk factors in young people - A. V. Sineglazova; A. Sh. Fakhrutdinova; T. Yu. Kim; S. D. Parve (Российский кардиологический журнал)
Aim. To study the relationship of lipitension and cardiometabolic risk (CMR) factors in young people.Material and methods. The case-control study on general obesity (GO) (overweight — 33,3%, GO — 33,3%) included 191 patients (Me=35,0 [30,0-39,0] years; F/M=97(50,8%)/94(49,2%)) without cardiometabolic diseases, comparable by sex and age. The prevalence and characteristics of lipitension were studied, taking into account the features of dyslipidemia and increased blood pressure (BP). Depending on the presence of lipitension, 2 groups were identified in which the CMR factors were studied: GO and abdominal obesity (AO), visceral fat, prediabetes, insulin resistance, increased C-reactive protein (CRP), hyperuricemia, glomerular filtration rate changes. Data were processed using SPSS Statistics 26.Results. Overall, the incidence of increased BP was 36,1%, hypertension (HTN) — 16,2%, and dyslipidemia — 73,3%. Lipitension was diagnosed in 25,1% of patients. At the same time, increased BP and HTN without combination with dyslipidemia were detected less frequently (13,1% and 5,2%, respectively). Dyslipidemia without increased BP and HTN, on the contrary, is more common (48,2%). Lipitension is more often diagnosed in men than in women — 32 (66,7%) and 16 (33,3%), p=0,005; [odds ratio=2,6; 95% confidence interval: 1,32-5,18]. In patients with lipitension, 43,8% were diagnosed with HTN, while the remaining 56,2% had BP ≥130/85 mm Hg. In the structure of dyslipidemia in lipitension, 79,2% had abnormalities in ≥2 lipid parameters, of which increased levels of low-density lipoprotein cholesterol (LDL-C) and hypercholesterolemia (78,3%) were most often detected. Persons with lipitension more often had AO (31,2%), increased glycated hemoglobin (HbA1c) >6% (39%) and insulin resistance (36,2%) than those without lipitension (p=0,026, p=0,018, p=0,044, respectively). With lipitension, a higher level of visceral fat (Me=8 [6-9] units) and HbA1c (Me=5,6 [5,1-6,0]%) was established than without it (Me=6 [4-9]U and Me=5,4 [5,1-5,9]%, respectively p=0,000 and p=0,018).Conclusion. Increased BP and HTN are more often found in combination with dyslipidemia than as an independent risk factor. In lipitension, the largest number of patients had ≥2 lipid metabolism disorders, most often represented by increased LDL-C and hypercholesterolemia. The presence of lipitension was associated with AO, increased HbA1c, and insulin resistance.